1986
DOI: 10.1002/art.1780290207
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Ro (SS‐A) and Anti‐La (SS‐B) in patients with Sjögren's syndrome

Abstract: Clinical, serologic, and genetic findings in Sjögren's syndrome patients were correlated with quantitative determinations for antibody against Ro (SS‐A), La (SS‐B), and nRNP (Sm) using newly developed, sensitive solid‐phase assays. In 86 Sjögren's syndrome patient sera, more than 96% had anti‐Ro (SS‐A), and 87% had anti‐La (SS‐B), spanning a 4.8 log10 range of autoantibody concentration, whereas only 95% of the patients had anti‐nRNP (Sm). Low levels of anti‐Ro (SS‐A) and anti‐La (SS‐B) were found in 10% and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
151
1
8

Year Published

1987
1987
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 320 publications
(175 citation statements)
references
References 35 publications
15
151
1
8
Order By: Relevance
“…Thus, it has been shown that approximately 90% of sera from primary SS patients are ANA positive on Hep-2 cells [26]. The finding that SS-B antibodies were more commonly detected in primary SS is in accordance with several previous reports [27]. Signs of polyclonal B cell activation and hypergammaglobulinaemia are commonly found in SS patients.…”
Section: Expression Of Activation Markers On T Cells Was a Prominentsupporting
confidence: 87%
“…Thus, it has been shown that approximately 90% of sera from primary SS patients are ANA positive on Hep-2 cells [26]. The finding that SS-B antibodies were more commonly detected in primary SS is in accordance with several previous reports [27]. Signs of polyclonal B cell activation and hypergammaglobulinaemia are commonly found in SS patients.…”
Section: Expression Of Activation Markers On T Cells Was a Prominentsupporting
confidence: 87%
“…Two criteria were selected to strictly define positive antibody binding: 1) reduction in the antibody binding or inhibition >70% by antigen in the antigen-inhibition ELISA, or >70% decrease in binding levels in the BSA-coated wells versus antigen-coated wells for the antigen-capture ELISA, and 2) a net antibody level greater than 3 SD above the mean of the level in the negative controls: 6,329 units in the anti-Ro ELISA, 2,068 units in the anti-La ELISA, and 3,226 units in the anti-Sm/nRNP ELISA. These criteria were purposefully more strict than those we used in previous studies that have shown antibodies to Ro in 14.5% and antibodies to La in 7.5% of normal sera (15)(16)(17)28).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, MHC control of these immune responses, either qualitatively or quantitatively, has been suggested. Recently, enzyme-linked immunosorbent assays (ELISA) have been developed to measure anti-Ro, anti-La, and the anti-Sdnuclear RNP (anti-SmhRNP) complex (14)(15)(16)(17)(18)(19)(20). By virtue of being more sensitive and quantitative, these assays may provide greater insight into the role…”
mentioning
confidence: 99%
“…Anti-Ro/SS-A antibodies in patients with SLE or Sjögren's Syndrome are very often accompanied by anti-La/SS-B antibodies and vice versa [21,22]. This phenomenon could be explained by hypothesizing a common (auto)antigenic particle as driving force behind both autoantibody responses.…”
Section: Introductionmentioning
confidence: 99%